Evaluation of lead‐based echodensities on transesophageal echocardiogram in patients with cardiac implantable electronic devices. (6th November 2022) - Patel, Neel J.; Singleton, Matthew J.; Brunetti, Ryan; Richardson, Karl M.; Bhave, Prashant D.
Abstract: Introduction: Transesophageal echocardiography (TEE) is recommended to rule out endocarditis in patients with cardiac implantable electronic devices (CIED). A lead‐based echodensity (LBE), however, is often found on TEE in patients with a CIED and may not represent an infection. We sought to evaluate the predictors, characteristics, and clinical significance of LBEs seen on TEE in patients with a CIED. Methods: Patients with a CIED were retrospectively identified from a database using International Classification of Diseases (ICD)‐9/ICD‐10 codes and were cross‐matched with Current Procedural Terminology codes for a TEE. Clinical and follow‐up data were collected. A blinded echo board‐certified cardiologist reviewed all TEEs. Results: Out of the 231 patients in the cohort, 191 had TEE performed for a noninfection‐related indication while 40 TEEs were part of an endocarditis workup. A total of 50 LBEs were identified, and a majority were in the noninfection cohort. Systemic anticoagulant use in the noninfection cohort was associated with a decreased odds of having LBE on TEE (odds ratio [OR] of 0.23 [95% confidence interval [CI]: 0.06–0.60, p = .003]). Lead dwell time in the noninfection cohort was associated with an increased odds of having LBE on TEE (OR 1.21 (95% CI: 1.04–1.39, p = .009]). Conclusion: In our cohort of patients who had TEE for noninfection indications we found that systemic anticoagulant use is associated with fewer LBEs on TEEs, suggesting possible thrombin fibrin composition of LBE.